2019
DOI: 10.2337/dc19-0145
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Medications and Mortality Risk in Individuals With Pancreatic Cancer–Related Diabetes and Postpancreatitis Diabetes: A Nationwide Cohort Study

Abstract: There are no specific treatment guidelines for diabetes of the exocrine pancreas. High-quality studies are warranted to investigate whether the use of antidiabetic medications has survival benefit in individuals with diabetes of the exocrine pancreas. The objective was to determine the risk of mortality associated with the use of antidiabetic medications in individuals with pancreatic cancer-related diabetes (PCRD) and postpancreatitis diabetes mellitus (PPDM). RESEARCH DESIGN AND METHODS Nationwide pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 51 publications
0
57
1
1
Order By: Relevance
“…There is some evidence that metformin has been associated with a significant reduction in cancer risk, although this has only been demonstrated in the setting of de novo cancer development . A recent retrospective cohort study demonstrated an association with significantly reduced mortality with metformin use in patients with diabetes post pancreatitis but this was not significant in the group post pancreatic surgery . Although there are no studies specific to the type 3c DM population, oral hypoglycaemic agents known to cause pancreatitis such as GLP‐1 agonists should be used with caution in this population with reduced residual pancreatic volume and recent instrumentation until further data is available to clarify if there is any increased risk of pancreatitis .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that metformin has been associated with a significant reduction in cancer risk, although this has only been demonstrated in the setting of de novo cancer development . A recent retrospective cohort study demonstrated an association with significantly reduced mortality with metformin use in patients with diabetes post pancreatitis but this was not significant in the group post pancreatic surgery . Although there are no studies specific to the type 3c DM population, oral hypoglycaemic agents known to cause pancreatitis such as GLP‐1 agonists should be used with caution in this population with reduced residual pancreatic volume and recent instrumentation until further data is available to clarify if there is any increased risk of pancreatitis .…”
Section: Discussionmentioning
confidence: 99%
“…New studies in recent years are springing up to clarify the question. [ 11 , 12 ] Therefore, here we perform a meta-analysis to assess the effect of metformin on survival outcome of pancreatic cancer patients with concurrent diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Although insulin is often administered for glycemic control in AP, 10,11 there is a dearth of evidence on the association between new use of insulin and risk of progression from AP to RAP and CP. To date, there is only indirect evidence-a 2017 population-based study from the United Kingdom followed 31,789 individuals with diabetes after AP or CP (individuals with progression from AP to CP were not specifically investigated) while considering insulin use as an end point, not an exposure.…”
mentioning
confidence: 99%